DC motor speed control using two quadrant DC Chopper based on Sliding Mode Controller - Arief, Fashly; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
DC motors are vital components in the industrial world, thanks to their ability to provide precise control over speed and torque. In various manufacturing processes, these motors are used to drive machines, conveyor systems, and other automated applications. However, the challenge faced is speed instability when the motor operates under variations in load and speed. To overcome this problem, this study focuses on controlling the speed of a DC motor using a two-quadrant DC chopper based on a Sliding Mode Controller (SMC). The SMC method has the ability to overcome disturbance models and provide consistent performance under dynamic conditions, making it very effective in maintaining the performance of a DC motor control system in various operational situations. In addition, the SMC is able to ensure the output system can track the desired reference and generate a control signal that minimizes tracking errors. The control signal in the SMC consists of two components, namely the reach mode and the slide mode. The design process in this study includes programming the Arduino Mega 2560 microcontroller, and the implementation of the SMC control system is carried out using MATLAB Simulink. Simulation results show that the SMC-based control can maintain a stable motor speed despite significant changes in load and speed. Thus, this research makes a significant contribution towards the development of more effective DC motor control systems for industrial applications